Consumptive Behavior of Muslim University Students Toward Sharia Fashion Products - Arlinda, Maileni; Abidin, Zaenal; Ahmad, Humaira; Febriansyah (CV. Zabags Qu Publish, 2026)
The development of sharia fashion in Indonesia not only reflects the growing religious awareness among Muslims but also reveals new dynamics in the consumption patterns of the younger generation, particularly university students. Amid the rising popularity of Islamic lifestyles and the strong influence of digital media, the consumption of sharia fashion has the potential to shift from need-based practices toward consumptive behavior imbued with symbolic meanings. This study aims to analyze the consumptive behavior of Muslim university students toward sharia fashion products and to identify the factors influencing such behavior from religious, social, psychological, and media-related perspectives. Employing a qualitative approach with a phenomenological strategy, data were collected through in-depth interviews, observations, and documentation involving Muslim students who actively consume sharia fashion products. The findings indicate that sharia fashion is perceived ambivalently as both a form of religious compliance and an expression of identity and modern lifestyle. Consumption decisions are shaped by the interaction of religious values, emotional impulses, social pressures, and exposure to social media and influencers, which in many cases trigger impulsive consumptive behavior. This study contributes to the literature on Muslim consumer behavior by offering a phenomenological understanding of the negotiation between religious values and contemporary consumer culture, as well as providing implications for strengthening Islamic consumption ethics literacy among university students.